Case Report: Intra-articular injection of tocilizumab for arthritis treatment in chronic graft-vs.-host disease - Xie, Mingyu; Liu, Qin; Yuan, Huiting; Chen, Yumei; Zou, Xian; Zhang, Zhenhong; Zhong, Baimao; Zeng, Huasong; Zeng, Haisheng (Frontiers in Pediatrics, 2025)
BackgroundChronic graft-vs.-host disease (cGVHD) is a major complication of allogeneic hematopoietic cell transplantation. It is a leading cause of long-term morbidity, non-relapse mortality, and impaired health-related quality of life. cGVHD is a multifactorial syndrome that can manifest with articular involvement. Approximately 50% of cGVHD survivors do not respond to glucocorticoid therapy used for arthritis. Subsequently, we shall present a case of a juvenile patient with arthritis and cGVHD, who responded well to intra-articular injection of tocilizumab, after bone marrow transplantation.Case pressentationA male adolescent with acute myeloid leukemia successfully underwent marrow stem cell transplantation. However, he developed arthritis in the elbow and knee joints and had difficulty walking more than 3 months after transplantation. He was administered anti-rejection drugs with cyclosporine, ruxolitinib, and methylprednisolone by his physician, which did not work. He was subsequently treated with intravenous tocilizumab under the supervision of his rheumatologist. Although his clinical symptoms showed remission at early stages, his knee joints were more swollen, and he could not stand after being infected with COVID-19. Both of his knee joints was injected with tocilizumab at 0, 2, 4, 6, 7, 11, and 19 weeks. Interleukin (IL)-6 levels in the peripheral blood continuously decreased. After treatment for 4 months, the patient could walk a few hundred meters with minimal exertion.ConclusionAn intra-articular injection of tocilizumab could be a viable treatment option for arthritis; however, large-scale clinical trials are warranted to confirm its efficacy.